2020
DOI: 10.1097/qco.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

What is new with hand hygiene?

Abstract: Purpose of review Healthcare-associated infections (HAIs) challenge healthcare systems worldwide. As healthcare workers’ hands are considered the main vector for transmission of pathogens, effective hand hygiene is the single most important action to prevent HAIs. We sought to highlight new developments and advances in hand hygiene. Recent findings Hand hygiene compliance averages at 38%. A sustained increase of compliance with a subsequent decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
1
16
0
3
Order By: Relevance
“…The implementation and promotion of compliance by the health professionals with safe hand hygiene practices have been the main concerns of current research studies on this topic. A number of studies have shown that compliance is still low in most care units and that it presents flaws in the process [11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…The implementation and promotion of compliance by the health professionals with safe hand hygiene practices have been the main concerns of current research studies on this topic. A number of studies have shown that compliance is still low in most care units and that it presents flaws in the process [11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of alcoholbased solutions was observed in only one (0.4%) opportunity before contact and in 83 (35.9%) after contact. It should be noted that the use of alcohol-based solutions has been strongly encouraged given the strong evidence of their effectiveness, ease of use, shorter application time, and greater skin tolerance as they cause less irritation (16)(17) . However, when the service takes place at home, the professional is required to take the product for this purpose and use it properly.…”
Section: Discussionmentioning
confidence: 99%
“…Hand disinfection is one of the most important measures to reduce the spread of nosocomial infections in hospitals [ 1 , 2 , 3 ]. The standard is to rub the hands for a typical duration of about 30 s to a few minutes [ 1 , 4 , 5 ] with liquid, mostly alcohol-based disinfectants [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%